Effectiveness of Peer-tutoring on Reading Comprehension of School Students in Hindi Language - Singh, Manju (JOURNAL OF INDIAN EDUCATION, 2010)
The present investigation was intented to study the effectiveness of peer-tutoring strategy as against conventional method of teaching Hindi language in terms of students’ reading comprehension. The quasi-experimental research design, i.e. pre-test-Post-test control group design was used and the study was conducted on a representative sample of 168 Class VIII students drawn from two schools of Agra district of Uttar Pradesh. It is evident from the analysis that peer-tutoring strategy has a significant role in enhancing the level of reading comprehension of eighth grade students in Hindi language. Further, experimental group students have made significantly higher gains in reading comprehension in comparison to their counter parts, i.e. conventional group students.